Prospecção de isolados de Trichoderma spp. com potencial de biocontrole, bioestimulo, indução de resistência e solubilização de nutrientes para cultura da soja - Russiano, Maira Cristina Schuster (2024)
Brazil is the largest producer of soybeans, with a planted area of 44 million hectares, making it the country's most exported commodity. Among the factors that limit crop yield, some diseases that cause rot in roots, stems and grains stand out, caused by phytopathogens that survive in crop remains, with some of the main causal agents being fungi: Macrophomina phaseolina, Fusarium spp. complex, Sclerotinia sclerotiorum and Diaporthe spp. complex Given the concern for human and environmental health, the use of biological control as a means of suppressing these phytopathogens has been gaining strength in recent years, with the genus Trichoderma as a highlight, due to the antagonist's broad mode of action, which includes competition, antibiosis, mycoparasitism and resistance induction. Therefore, the objective of the work was to prospect isolates of Trichoderma spp. present in the soil, evaluate their potential mechanisms of action, to be used in the biological control of soil diseases that affect soybeans. The experiments were carried out at the Federal Technological University of Paraná, Campus Dois Vizinhos. To search for native isolates of Trichoderma spp., nylon bags containing sclerotia of Sclerotinia sclerotiorum were used, which were distributed in 28 points on the university's experimental farm, placed among the soil and crop residues. The bags were collected after 20 days, and the sclerotia with a visual appearance of colonization by a biological agent were transferred to Petri dishes in order to isolate the microorganisms; obtaining four isolates of Trichoderma koningiopsis. With the four isolates, the morphology of the hyphae was studied, antagonism test with M. phaseolina, F. tucumaniae, S. sclerotiorum and D. longicolla; antibiosis test of filtered metabolites; and antibiosis by volatile organic compounds. The solubilization capacity of phosphorus in NBRIP medium, potassium in Pikovskara medium, and nutritional analysis of the sap using the Nir equipment were also evaluated. In a greenhouse, the four isolates of Trichoderma spp. were applied. in soybeans, to carry out resistance induction analyzes in soybean plants, which include: determination of chitinase, β 1,3 glucanase, total proteins, phenylalanine ammonialyase and phenolic compounds. The growth promotion test was also conducted in pots, evaluating the aerial part and root system of the plants. The design adopted was completely randomized with four replications. The data obtained were subjected to the Shapiro-Wilk normality test, ANOVA followed by regression analysis in the Rbio software. With the results obtained, it can be seen that the ideal growth range for Trichoderma koningiopsis is between 25 and 30 °C. They were efficient in in vitro control of the phytopathogens under study, obtaining action in competition, mycoparasitism and antibiosis of volatile organic compounds; however, they did not demonstrate efficiency with the MIC methodology using filtered metabolites. They proved to be efficient in solubilizing phosphorus and potassium, and in inducing resistance, increasing the accumulation of glyceolin in cotyledons, and activating chitinase and β 1,3 glucanase. Growth promotion capacity was also observed in soybean plants treated with the isolates.